Bimbingan Karier Berbasis Teori Karier Trait and Factor untuk Meningkatkan Perencanaan Karier Siswa - Lodiati Selan; Joris Taneo; Erly Oviane Malelak (Institut Agama Kristen Negeri Kupang, 2024)
The phenomenon in the field shows a lack of understanding of student career planning. The product in conducting research using the ADDIE model. Researcher used a validation questionnaire tested by the validator to conduct a test and the results of the validation of the material expert with a percentage value of 83.6%, validation of the design expert with a percentage value of 80%, validation of the practitioner expert with a percentage value of 80% so that the career guidance service guide based on the trait and factor career theory was declared very feasible. The results of the experiment can be seen from the pre-test and post-test carried out by students by answering 10 questions. These results show that the post-test value is greater, namely 86% compared to the pre-test value with a value of 67.2%. Thus, the career guidance product based on the trait and factor career theory can be used in the career guidance service process.